IMPLEMENTASI WEIGHT PRODUCT DALAM PEMILIHAN JENIS TANAMAN HIDROPONIK - Laksamana, Aditia; Ramdhan, William (Jurnal Manajamen Informatika Jayakarta, 2024)
Hydroponic plant cultivation is the cultivation of plants in the agricultural sector that uses water as a medium for plant growth and development so that it is an efficiency effort with the availability of agricultural land. Hydroponics has an impact on improving aesthetics, genetic transformation, and supporting nature conservation. Based on this, customers who cultivate hydroponic plants are increasing. The problem faced at Sahabat Hidroponik is the difficulty of determining plants that suit customer needs. To overcome this problem, a decision support system approach was carried out using the Weighted Product method. The decision support system provides recommendations to customers by ranking alternative hydroponic plants based on the weight of the assessment criteria according to the customer's desired needs. The criteria used in this research are water requirements, nutritional requirements, plant population, seed prices, harvest time. The recommendation results are not the final results that must be taken, but rather recommendations that can be used by customers in determining their decisions regarding hydroponic plants.